The Role of Principal Leadership Management as a Driving Force in Implementing the Independent Curriculum Using AI - Yuni, Sri; Saryanto, Saryanto; Rejokirono, Rejokirono (Malikussaleh University, Aceh, Indonesia, 2025)
In the millennial era, characterized by constant change and progress, schools that thrive possess specific qualities and characteristics. Education not only functions as a place to transfer knowledge but also as a place to develop students' skills, character, and critical thinking abilities. In this increasingly complex world, educational institutions must adapt curricula and teaching methods that are relevant and able to meet students' diverse needs. Schools that innovate and provide captivating learning experiences will be better able to attract the attention of students and parents. In addition, educational institutions must realize the importance of building an identity and characteristics that distinguish them from other schools. This includes developing superior programs, adequate facilities, and a positive and supportive learning environment. This study investigates the role of principal leadership in implementing the Merdeka Curriculum while integrating artificial intelligence (AI) in a kindergarten/early childhood education environment. Through a qualitative approach, this study explores the experiences of a principal and staff at TK IT Tunas Mulia. Findings indicate that principals play a critical role in fostering a culture of innovation and adaptation to AI, providing the necessary training and resources for teachers to utilize AI tools effectively, and collaborating with stakeholders to ensure successful implementation. However, the study has identified challenges such as limited teacher proficiency in AI and the need for more comprehensive AI-integrated curriculum materials. While principal leadership plays a critical role, the study concludes that further support and professional development are necessary to fully harness the potential of AI in improving early childhood education.